Analisis Market Timing Ability Dan Stock Selection Skill Manajer Investasi Reksa Dana Saham Di Indonesia Periode 2007-2012 - , Aditya Wisnuwardana ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the performance of equity mutual fund in Indonesia by looking at the ability of market timing and stock selection. Performance measurements carried out by the method of measurement with riskadjusted measures equipped with an analysis by the method of Treynor-Mazuy (1966). This study uses monthly data NAV / Unit of equity mutual fund in Indonesia 2007-2012 period based on a sample of 10 firms of the Investment Manager. From the result of this study, concluded that the performance of equity mutual fund GMT Dana Ekuitas is managed by PT. GMT Aset Manajemen as manager of the investment, scored the highest performance of the 10 samples that had been taken while BNI Dana Berkembang performance is the smallest value as well underperformed. In this study, it was found that nine out of ten samples of the equity mutual fund managed by all fund managers with a positive value indicates the probability of t-statistic values are not significant at the Î± = 5 percent. Only BNI Dana Berkembang is managed by PT. BNI Securities showed negative results. Thus, since the probability of t-statistics are not significant at the Î± = 5 percent, it can be concluded that the equity mutual fund managed by investment managers in this study do not have market timing and stock selection ability by individual test. By using a panel data regression for the entire test on the model of Treynor-Mazuy, it can be concluded that the investment manager in Indonesia do not have a stock selection skill and market timing ability. This is evidenced by the coefficient Î±p and Î²pt positive but not statistically significant.